Mature placental teratoma, fetiform type: a rare case report - Verma, Trishika; Seema; Kaur, Manmeet; Burman, Kanika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
A placental teratoma is a rare benign tumor of germ cell origin. Fewer than 50 cases have been reported worldwide. The fetiform variant poses a diagnostic challenge in distinguishing it from acardius amorphus, as it resembles fetal structures without true axial organization. Here we present a case of mature placental teratoma, fetiform type, in a 34-year-old G2P1L1 woman who delivered a healthy male infant at term via uncomplicated vaginal delivery. Post-delivery, a 7.0×6.5×3.5 cm hairy mass was identified on the fetal surface of placenta, supplied by placental vessels without Wharton's jelly or an umbilical cord. The tumor was not reported on antenatal scans. On Gross examination, a heterogeneous solid mass with yellowish areas and few bony components was identified; histopathology confirmed mature tissues from all three germ layers, including ectoderm, mesoderm, endoderm, without immature, malignant, or any organized fetal structures. Due to absent axial skeleton, polarity, and segmentation diagnosis favours teratoma over acardius amorphus. Etiology suggests aberrant migration of germ cells between amnion and chorion. There were no adverse neonatal or maternal outcomes in our case. This case report adds to the limited literature of placental teratoma.